Manipulasi Informasi Pada Korban Love Scamming Di Media Sosial - Novema Kumalasari; Sri Herwindya Baskara Wijaya (Universitas Sebelas Maret (UNS), 2024)
Love scamming is a troubling cybercrime in 2020 with 199 victims experiencing a total loss of 13 billion rupiah (Pangalila, et al., 2023). One of the cities prone to love scamming cases is Semarang City. Love scamming cases occur because there is high interaction from the perpetrator to the victim to manipulate information. Therefore, this study aims to explore the process of information manipulation that occurs in female victims of love scamming in Semarang City through social media. The theory used in this research is the Interpersonal Deception Theory (IDT) because it aims to analyze deceptive messages in interpersonal communication, especially in exploring the process of information manipulation in love scamming cases. This research uses a qualitative method with a case study approach. The object in this study is the manipulation of information on victims of love scamming cases. The sampling technique used purposive sampling with five informants. The data sources in this study consist of primary data and secondary data. Data collection techniques using interviews and documentation. Data validity in this study was carried out by increasing persistence. The data analysis technique in this study uses the Cresswell model. The results of the study found that the process of information manipulation in the case of love scamming occurs through five stages consisting of setting up a social media profile (the profile), establishing interpersonal relationships, increasing intimacy (grooming), creating scenarios to ask for money (the string), as well as terminating relationships and disclosing secrets (revelation). In these stages, there are several forms of information manipulation that occur, namely self-identity manipulation, trust manipulation, emotional manipulation, crisis manipulation, and authority manipulation.